2022
DOI: 10.2186/jpr.jpr_d_20_00184
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of implant placement with computer-guided surgery in partially edentulous patients and possible influencing factors: A systematic review and meta-analysis

Abstract: Purpose: To review the current clinical studies regarding the accuracy of implant computer-guided surgery in partially edentulous patients and investigate potential influencing factors. Study selection: Electronic searches on the PubMed and Cochrane Central Register of Controlled Trials databases, and subsequent manual searches were performed. Two reviewers selected the studies following our inclusion and exclusion criteria. Qualitative review and meta-analysis of the implant placement accuracy were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 52 publications
(118 reference statements)
2
64
0
Order By: Relevance
“…Also, no clinical studies appear to be available that have systematically investigated the effect of using a pinhole drill guide yet. Despite this lack of available reference data, the observations in this study are well in line with studies that analyzed the effects of the type of guide support on implant placement accuracy 16,30) . In this context, it is also interesting to note that anchoring pins displayed a relatively higher placement accuracy when com-pared to implants.…”
Section: )supporting
confidence: 86%
See 1 more Smart Citation
“…Also, no clinical studies appear to be available that have systematically investigated the effect of using a pinhole drill guide yet. Despite this lack of available reference data, the observations in this study are well in line with studies that analyzed the effects of the type of guide support on implant placement accuracy 16,30) . In this context, it is also interesting to note that anchoring pins displayed a relatively higher placement accuracy when com-pared to implants.…”
Section: )supporting
confidence: 86%
“…Specifically, the indication and patient-individual anatomic preconditions have been reported to affect implant placement accuracy significantly. This effect was mainly attributed to differences in the availability of anatomical structures for landmarking during virtualization and the type of tissues that may be used to support the surgical guide 30,34) . .…”
Section: )mentioning
confidence: 99%
“…Based on the literature, the error factors can be classified in three categories (i) clinical situation derived factor [8,9], (ii) implant system derived factors [10] and (iii) surgical guide design [11,12] and manufacturing derived factor [13,14]. For example, Putra et al [15] showed in a literature review that guides produced by a conventional method induce a higher angular deviation than a 3D-printed guide.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, cur-rent prosthodontic treatments are closely related to digital dentistry. This issue of JPR contains several topics covering digital technologies, such as digital impression [4] and computer-aided design and manufacturing (CAD/CAM) [5] for digital dentures, implant computer-guided surgery [6] and 3D printing [7]. In addition, a review article by Kishimoto et al on dental applications of artificial intelligence (AI) [8] illustrates the dawning of a new era, in which digital data provide effective diagnosis and suitable treatment planning for future prosthodontic treatments.…”
Section: Dear Readersmentioning
confidence: 99%